2007
DOI: 10.1109/jlt.2007.901325
|View full text |Cite
|
Sign up to set email alerts
|

Migration Strategies Toward All Optical Metropolitan Access Rings

Abstract: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription technology is expected to become mature in the medium term, and it may be used as an alternative to current OCS networks, due to its potential advantages in terms of bandwidth allocation granularity. While OBS is being extensively studied in the literature, little attention has been paid to comparative analysis of OBS versus OCS, specially concerning cost analysis. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Essentially, the traditional digital subscriber line (DSL) and coaxial cable (COAX) networks were evaluated in terms of up/downstream bandwidth (BW), packet latency and packet loss. The measured link BWs were much lower than future residential BW requirements, which have been estimated in the range from 2/20 Mbps [3] to 30/100 Mbps [4]. Additionally, although measured bandwidths have been observed highly asymmetrical, the authors in [5] have shown that traffic patterns are becoming more and more symmetrical.…”
Section: Introductionmentioning
confidence: 69%
“…Essentially, the traditional digital subscriber line (DSL) and coaxial cable (COAX) networks were evaluated in terms of up/downstream bandwidth (BW), packet latency and packet loss. The measured link BWs were much lower than future residential BW requirements, which have been estimated in the range from 2/20 Mbps [3] to 30/100 Mbps [4]. Additionally, although measured bandwidths have been observed highly asymmetrical, the authors in [5] have shown that traffic patterns are becoming more and more symmetrical.…”
Section: Introductionmentioning
confidence: 69%
“…Unlike the above-referenced papers, in this work we address the scenario in which failures can propagate, through the GMPLS control plane from one node to its neighbours, and once the control plane functionality is affected, it is possible that the data plane is affected as well thus creating the two-dimensional failure propagation scenario discussed in the introduction. We focus on optical ring networks for two reasons: First, they are widely deployed as part of several transport technologies and are commonly found in metropolitan area networks [15,39]. Second, their structure lend itself amenable to the study of the evolution of failures and the effects on reliability through continuous-time Markov chains, as will be discussed in the following sections.…”
Section: Failures In Gmpls-based Networkmentioning
confidence: 99%
“…For example, to date, the architectures of OBS-based wide area network, 3 metropolitan area network, 4 and access network 5 have been developed and verified by theories.An all-optical four-wavelength 3R burst mode regenerator based on semiconductor optical amplifier-based Mach-Zehnder interferometer has been presented. 1,2 A variety of OBS-based optical networking technologies and architectures have been developed and verified in recent years.…”
Section: Introductionmentioning
confidence: 99%